Országalma - Pálos, György; Czabán, György (Hungary : Közgáz Vizuális Brigád, 1998)
In the funny, lyrically absurd story, two enthusiastic employees of Bábolna TV head to BAZ County, Baktakék and Csenyéte, to follow Csulánó, the famous gypsy coupe. They learn that Csulánó met the devil, that he had stolen a policeman's helmet, that an unknown lieutenant had appeared on the outskirts of the village, who had seduced the coupe's daughter, Mariska, and how the luxurious wedding had taken place. Along the way, many other old and new tales come to life.
Romology Film Collection
Keywords: Fiction films